Relativistic Magnetohydrodynamics with Application to Gamma-Ray Burst Outflows. II. Semianalytic Super-Alfvénic Solutions - Vlahakis, Nektarios; Königl, Arieh (The Astrophysical Journal, 2003)
We present exact radially self-similar solutions of special relativistic magnetohydrodynamics representing ``hot'' super-Alfvénic outflows from strongly magnetized, rotating compact objects. We argue that such outflows can plausibly arise in gamma-ray burst (GRB) sources and demonstrate that, just as in the case of the trans-Alfvénic flows considered in the companion paper, they can attain Lorentz factors that correspond to a rough equipartition between the Poynting and kinetic energy fluxes and become cylindrically collimated on scales compatible with GRB observations. As in the trans-Alfvénic case, the initial acceleration is thermal, but, in contrast to the solutions presented in the companion paper, part of the enthalpy flux is transformed into Poynting flux during this phase. The subsequent, magnetically dominated acceleration can be significantly less rapid than in trans-Alfvénic flows.
Keywords: Astrophysics; galaxies: jets; Gamma Rays: Bursts; ISM: jets and outflows; magnetohydrodynamics: MHD; methods: analytical; relativity